PENGARUH KEPERCAYAAN, PENGALAMAN PEMBELIAN, DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SECARA ONLINE - EKA SARI, SELVI (JURNAL WIDYA GANECWARA, 2020)
This      study   aims to     determine the      effect of   trust, experience and   ease of   use partially and simultaneously on the decision to purchase products online at Batik Batik University Students in Surakarta. This      type of      research    is quantitative.      The population      in  this      study    were  students  of  the  Faculty  of  Economics  Regular Morning Study Program 7, totaling 300 people. The sampling technique used incidental sampling of 100 respondents. This study uses data analysis techniques in the form of multiple linear regression test. The results of this study indicate that: (1) There is an influence of Trust on Online Product Purchasing Decisions in Students of Surakarta Batik Islamic University (2) There is an influence of  Experience on Online Product Purchasing Decisions on Students of Batik Surakarta Islamic University (3) There was no influence  of  Ease  of  Use  on  Online  Product  Purchasing  Decisions  of  Batik  Batik University  Students  in  Surakarta  (4)  There  is  a  simultaneous  influence  of  Trust, Experience and Ease of Use on Online Purchasing Decisions of Batik Islamic University Students